PENGARUH KONSENTRASI IBA (INDOLE BUTYRIC ACID) DAN JENIS MEDIA TANAM TERHADAP PERTUMBUHAN BIBIT NANAS (Ananas comosus [L.] Merr) ASAL TUNAS MAHKOTA - Fidia Octavia Sari Octavia Sari; Rugayah Rugayah; Yohannes C. Yohannes C. Ginting (Jurnal Agrotek Tropika, 2014)
The research was conducted to determine the effects of IBA concentration on the growth of pineapple seedlings sprout from crown cutting on each type of growing media. The treatment was arranged in factorial (5x2) in randomized block design with three replications. The first factor is the concentration of IBA (A), which consists of: without IBA (A0), IBA 100 ppm (A1), IBA 200 ppm (A2), IBA 400 ppm (A3), and IBA 600 ppm (A4). The second factor is the type of planting medium (B), which consists of river sand (B1) and volcanic sand (B2). The results showed that the concentration of IBA 600 ppm treatment effect on seedling growth shown by the increasing number of roots produced. Treatment planting medium used had no effect on all observed variables. IBA concentration on root wet weight depending on the type of planting medium used.